2023
DOI: 10.15587/1729-4061.2023.293511
|View full text |Cite
|
Sign up to set email alerts
|

Development of the automated decision-making system synthesis method in the management of information security channels

Olexander Shmatko,
Serhii Herasymov,
Yurii Lysetskyi
et al.

Abstract: In the process of transmission channels functioning, the results of the work of bodies for detecting and blocking information leakage channels are not sufficiently taken into account. Management of information protection channels is actually the collection and display of data followed by the assignment of influence on each information channel separately and is carried out in manual mode. In decision support systems, the tasks of identifying information leakage channels are not solved. There is a contradiction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…In [17], two-factor authentication is used, when the authorization code is sent through a separate channel. This approach, admittedly, is associated with significant overhead costs associated with both the use of additional channels and the need for additional processing.…”
Section: Fig 1 Example Of Social Connections Of Social Network Agentsmentioning
confidence: 99%
“…In [17], two-factor authentication is used, when the authorization code is sent through a separate channel. This approach, admittedly, is associated with significant overhead costs associated with both the use of additional channels and the need for additional processing.…”
Section: Fig 1 Example Of Social Connections Of Social Network Agentsmentioning
confidence: 99%
“…To build multi-contour security systems, let's use a threat classifier that takes into account hybridity, synergy and integration of mixed threats with social engineering methods. The practical implementation of the classifier is given in the resource [39], the main stages of the formation of a multi-contour information security system for socio-cyberphysical systems [6,40,41].…”
Section: Materials and Research Methodsmentioning
confidence: 99%
“…Analysis [1][2][3] showed that the use of HCCC provides a significant reduction in the complexity of generating (≈12 times) and decoding (≈20 times) a cryptogram compared to the McEliece crypto-code construction on classical codes. At the same time, HCCC can be built over the GF(2 4 -2 6 ), which allows reducing computational and capacity costs, while resistance is ensured by transmitting damaged text and damage (the "reduction" rules in each plaintext character).…”
Section: Causing Damagementioning
confidence: 99%
See 1 more Smart Citation
“…The conducted analysis [2,3,5] shows that expert methods and the method based on the calculation of the correlation between the characteristics are most often used to determine the dependence between the characteristics [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Literature and Problem Statementmentioning
confidence: 99%